The Effect of Vitamin D Supplementation on Blood Lipids in Patients with Polycystic Ovary Syndrome: A Meta-Analysis of Randomized Controlled Trials. (31st January 2021) - Gao, Hong; Li, YanTao; Yan, WenNan; Gao, Fei
Abstract : Purpose . Studies have found that vitamin D supplementation may improve blood lipids in patients with polycystic ovary syndrome, but the results are controversial, so this study will further analyze the effect of vitamin D supplementation on blood lipids in patients with polycystic ovary syndrome. Methods . PubMed, Embase, Cochrane Library, CNKI, and Wanfang databases were searched up to May 2020, to identify randomized controlled trials of the effect of vitamin D supplementation on blood lipids in patients with polycystic ovary syndrome. The Cochrane risk of bias tool was applied to assess the risk of bias, and RevMan5.3 software was used for statistical analysis. Results . Ten studies were included in this study, including 543 subjects. The results of the meta-analysis showed that, compared with placebo, vitamin D supplementation can significantly reduce total cholesterol level (WMD = –11.32, 95% CI = [–14.51, –8.41], P < 0.00001 ), low-density lipoprotein cholesterol level (WMD = –4.83, 95% CI = [–7.52, –2.14], P = 0.0004 ), and triglyceride level (WMD = –8.23, 95% CI = [–13.08, –3.38], P = 0.0009, but the effect on high-density lipoprotein cholesterol level is not statistically significant (WMD = –0.32, 95%CI = [–1.24, 0.60], P = 0.50 ). Conclusion . Vitamin D supplementation can significantly reduce total cholesterol, low-density lipoprotein cholesterol, and triglycerides in patients with polycystic ovary syndrome. However, it has no significant effect on high-density lipoprotein cholesterol.